2003
DOI: 10.1053/joca.2002.0861
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid features and their relations to osteoarthritis severity: new findings from sequential studies

Abstract: As noted before CPPD and apatite crystals were more common in patients with more severe OA. New findings are that our sequential cases showed that there were some patients with no crystals at onset but that crystals appeared with progression of the disease. Fibril presence in SF also correlated with progression of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(106 citation statements)
references
References 23 publications
5
92
0
8
Order By: Relevance
“…Fuerst and colleagues' report reinforces the hypothesis of a pathologic role of BCPs in OA, as previously suggested by numerous clinical and laboratory studies such as that reported by Nalbant and colleagues, which showed that the presence of BCPs in OA synovial fluid (SF) predicted increased cartilage destruction (2). In vivo, in OA animal models such as guinea pig and STR/ort mouse models, meniscus calcifications preceded cartilage breakdown (3,4).…”
Section: To the Editorsupporting
confidence: 72%
“…Fuerst and colleagues' report reinforces the hypothesis of a pathologic role of BCPs in OA, as previously suggested by numerous clinical and laboratory studies such as that reported by Nalbant and colleagues, which showed that the presence of BCPs in OA synovial fluid (SF) predicted increased cartilage destruction (2). In vivo, in OA animal models such as guinea pig and STR/ort mouse models, meniscus calcifications preceded cartilage breakdown (3,4).…”
Section: To the Editorsupporting
confidence: 72%
“…In vitro, calcium-containing crystals induce the release of catabolic cytokines and proteases from synovial cells and chondrocytes (Cheung 2001). Clinically, their presence predicts increased severity of joint damage and more rapid progression of joint destruction (Ledingham et al 1993;Nalbant et al 2003). …”
Section: Introductionmentioning
confidence: 99%
“…BCP crystal deposition in knee articular cartilage is correlated with cartilage destruction and more severe lesions (1). Their presence in synovial fluid predicts radiological OA progression (3). Extra-articular depositions of BCP crystals are mostly asymptomatic but can give rise to acute inflammatory attacks.…”
mentioning
confidence: 99%